One-dimensional single-helix coordination polymer self-assembled by a crown-ether appended-N-heteroacene radical anion. Issue 35 (6th August 2019) - Isoda, Kyosuke; Takahashi, Hinako; Mutoh, Yuichiro; Hoshino, Norihisa; Akutagawa, Tomoyuki
Abstract : Radical anions based on crown-ether appended N-heteroacene with Na + self-assemble one-dimensional helical coordination polymers. Abstract : A crown-ether appended N-heteroacene1 was reduced in the presence of NaBPh4 to the radical anion2 by accepting one electron transferred from both the cathode and BPh4 – as a reductant. The obtained radical anion2 can function as a radical anion ligand to bridge two sodium ions to self-assemble into one-dimensional helical coordination polymers.